Construction de l'Est et de l'Ouest : vers des compétences interculturelles. Un exemple de recherche à Hong-Kong en situation de mobilité académique - Martinez, Valérie (fi=Turun yliopisto|en=University of Turku|, 2016)
Numerous scholars have already stressed the need to prepare students prior to academic mobility (Abdallah-Pretceille, 2003; Jackson, 2013, for example) in order to face hypermodernity (Aubert, 2004). As per the new mobilities paradigm (Urry, 2007), this implies considering individuals at the centre of political and institutional issues. Furthermore, the multiplicity of terminology of references towards academic mobility, and intercultural competences, justifies this research. The theory, for this doctoral dissertation, applies “renewed interculturality” (Dervin, 2012), a move away from a culturalist approach. Intercultural competences are therefore defined as a stepping back from discourses on the Other that may emerge during encounters. In order to collect the data, six focus groups have been organised with two batches of students from a Higher Education Institution in Hong-Kong, an “education hub” (Dervin & Machart, 2014) that is striving to be competitive particularly in increasing the number of incomingand outcoming students. Training and education to interculturality have been implemented prior to academic mobility in order to observe the impact on participants’ discourses before and after the mobility. Theories of enunciation and dialogism represent the methodology allowing us to compare and analyse the reported voices in the participants’ discourse and their prosodic realisation (Martin & White, 2005) before and after the experience of academic mobility. I have attempted to observe the dialogic space available to welcome the Other during encounters in the participants’ discourse. The results seem to underline the increased number of reported voices in participants’ discourse after study abroad, but as the space opened for negotiation is instable and depends on the interlocutors and the voices addressed, consequently, further research appears necessary to study the influences of a preparation prior to mobility on the contraction or expansion of heteroglossia. All in all, this doctoral dissertation aimed to renew preparation